2020
DOI: 10.1086/704615
|View full text |Cite
|
Sign up to set email alerts
|

Parental Leave Benefits, Household Labor Supply, and Children’s Long-Run Outcomes

Abstract: We study how parental leave benefit levels affect household labor supply, family income, and child outcomes, exploiting the Speed Premium (SP) in the Swedish leave system. The SP grants mothers higher benefits for a subsequent child without re-establishing eligibility through market work, if two births occur within a pre-specified interval. We use the spacing eligibility cutoffs in a Regression Discontinuity framework and find that the SP improves educational outcomes of the older child, but not of the younger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 74 publications
(79 reference statements)
0
18
0
Order By: Relevance
“…For adults, we study depression and anxiety, which are also some of the most common mental illnesses in Sweden (Socialstyrelsen 2013), and which have been shown to be related to ADHD diagnosis in childhood. 11…”
Section: A Mental Health Outcomesmentioning
confidence: 99%
“…For adults, we study depression and anxiety, which are also some of the most common mental illnesses in Sweden (Socialstyrelsen 2013), and which have been shown to be related to ADHD diagnosis in childhood. 11…”
Section: A Mental Health Outcomesmentioning
confidence: 99%
“…3 Carneiro et al (2015) use a similar argument to explain their findings of why a 4-month paid maternity leave introduction had significant (positive) impact on child outcomes in Norway while the previous literature had not found any effects. Parental leave taken by mothers plays a role for children's outcomes (Ginja et al, 2020), but leave taken by fathers does not improve the long-run gender balance in housework (Ekberg et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the 1995 reform on parental leave uptake has previously been studied by Ekberg, Eriksson, and Friebel (2013), who find strong short-term increases in fathers' parental leave take-up, but find no spillover effects on the long-term division of household work. 2,3 Furthermore, Eriksson (2005) evaluated the effect of the second "daddy-month" in 2002 and found that this reform further increased fathers' average parental leave take-up from one to around two months.…”
Section: A Introduction Of Paternity Leave Quotasmentioning
confidence: 99%